2016
DOI: 10.2147/ott.s98875
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol suppresses proliferation and invasion in human oral squamous cell carcinoma

Abstract: Carvacrol, a component of thyme oil, as a novel antitumor agent, has been implicated in several types of cancer cells. However, the mechanisms underlying the effect of carvacrol in human oral squamous cell carcinoma (OSCC) remain unclear. Here, we report that carvacrol significantly inhibits tumor cell proliferation, metastasis and invasion, and induces apoptosis in OSCC. Our results demonstrated that the molecular mechanisms of the effect of carvacrol in Tca-8113 induces G1/S cell cycle arrest through downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 32 publications
5
37
0
Order By: Relevance
“…Several monoterpenes including linalool were reported to act as antiproliferative agents against cancer cells by inducing cell growth arrest, both at G0/G1 [21,29] or G2/M [22,30]. In our study, linalool promoted a time and dose-dependent inhibition of cell growth, as indicated by the WST-1 assay.…”
Section: Discussionsupporting
confidence: 61%
“…Several monoterpenes including linalool were reported to act as antiproliferative agents against cancer cells by inducing cell growth arrest, both at G0/G1 [21,29] or G2/M [22,30]. In our study, linalool promoted a time and dose-dependent inhibition of cell growth, as indicated by the WST-1 assay.…”
Section: Discussionsupporting
confidence: 61%
“…[55,58] Similarly, high levels of MMP2 in venous leg ulcers and diabetic foot ulcers [58] also seem to hinder the wound healing. In this context, carvacrol and thymol are also able to downregulate MMP9 and MMP2 in several experimental conditions [41,[59][60][61][62] and these effects can be interesting to the management of chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…17 Carvacrol is a natural monoterpenic phenol, which has been reported to suppress cell proliferation and invasion in human oral squamous cell carcinoma. 18 Chen et al 19 demonstrated that carvacrol suppresses glioblastoma cell proliferation, migration, and invasion. Besides, carvacrol was revealed to inhibit cell proliferation, migration, and invasion of prostate and colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%